The president's wife : a novel - Wood, Tracey Enerson (Sourcebooks Landmark, 2023)
"Socialite Edith Bolling has been in no hurry to find a new husband since she was widowed, preferring to fill her days with good friends and travel. But the enchanting courting of President Woodrow Wilson wins Edith over and she becomes the First Lady of the United States. The position is uncomfortable for the fiercely independent Edith, but she's determined to rise to the challenges of her new marriage--from the bloodthirsty press to the shadows of the first World War. Warming to her new role, Edith is soon indispensable to her husband's presidency. She replaces the staff that Woodrow finds distracting, and discusses policy with him daily. Throughout the war, she encrypts top-secret messages and despite lacking formal education becomes an important adviser. When peace talks begin in Europe, she attends at Woodrow's side. But just as the critical fight to ratify the treaty to end the war and create a League of Nations in order to prevent another, Woodrow's always-delicate health takes a dramatic turn for the worse. In her determination to preserve both his progress and his reputation, Edith all but assumes the presidency herself. Now, Edith must contend with the demands of a tumultuous country, the secrets of Woodrow's true condition, and the potentially devastating consequences of her failure. At once sweeping and intimate, The President's Wife is an astonishing portrait of a courageous First Lady and the sacrifices she made to protect her husband and her country at all costs"--